Determinan Kejadian Stunting pada Balita Usia 24-59 bulan di Kecamatan Pujer Kabupaten Bondowoso - Sulistyani; Ira Dwi Susanti; Ninna Rohmawati (Jurnal Kesehatan, 2021)
Stunting is one of the nutrition problems that a still concern throughout in the world. Indonesia is the third country which highest prevalence of stunting in the Southeast Asia. In East Java, one of priority districts for handling stunting is Bondowoso Regency. Pujer disrict was sub-district with the highest prevalenced of stunting in Bondowoso Regency on 2020. The prevalenced of stunting in August 2018 was 25.36%, in February 2019 of 24.70%, in August 2019 of 26.73%, and in February 2020 it was 27.66%. This research purpose to know determinants of stunting on age toddler  24 - 59 mount in Pujer Distric,Bondowoso Regency. The research method uses an observational analytic with a cross sectional design. The research sample was 84 toddlers aged 24-59 months. The sampling technique using simple random sampling. The data collection technique using quetionnarie with interwieving on monher’s toddler and the data were analyzed using the chi-square test with a significance of p <0.05. The results univariate analysis was coulded most of the toddler were not stunting at 67.9% and the toddler were stunting at 32.1%. The results of bivariate analysis showed that there was no relationship between energy consumption (0.053), protein consumption (0.456), infectious diseases (0.771), history of BBLR (0.381), and exclusive breastfeeding (0.739) with the incidence of stunting in toddler in Pujer District, Bondowoso Regency.